THE EFFECT OF BOILING TIME AGINT THE PHYSICAL PROPERTIES, CHEMICAL PROPERTIES, AND ORGANOLEPTIK OF PORK SKIN CRAKERS - Bastari Sabtu; Imanuel Hermanus Lobo Lay; Heri Armadianto (Journal of Tropical Animal Science and Technology, 2021)
The purpose of this study was to determine the effect of boiling time on the chemical, organoleptic properties of pork skin crackers. The materials used in this study were pork skin, lime solution, seasonings and cooking oil. The design used was a completely randomized design consisting of 4 treatments and 3 replications. The treatments were boiling for 5 minutes (R0), boiling time for 10 minutes (R1), boiling time for 15 minutes (R2), and boiling time for 20 minutes (R3). The results showed that the treatment had no significant effect (P> 0.05) on protein content, fat content, collagen, and organoleptic tests which included color, taste, crispness, level of preference, and shape of pork skin crackers. In conclusion, boiling can be done for 5 - 20 minutes, but to produce optimal skin crackers, boiling can be done for 15-20 minutes.